Effects of a novel hindered phenol samarium complex on the thermo-oxidative aging of styrene-butadiene rubber/silica composites. (March 2021) - Sun, Yangkun; Huang, Jizhong; He, Jingwei; Tang, Zhenghai; Zhu, Lixin; Liu, Fang
Highlights: A novel hindered phenol rare earth complex (DTSm) was prepared by a simple and environmentally friendly method. The hindered phenol rare earth complex could significantly enhance antioxidative efficiency of SBR/silica composites for a much longer time compared with commercial antioxidant BHT. DTSm had excellent thermal stability, volatility resistance, solvent extraction resistance while had no negative effect on color of the SBR/silica composites. Abstract: A novel rare-earth complex containing hindered phenol groups (DTSm) was prepared through coordination reaction between 3, 5-di- tert -butyl-4-hydroxybenzoic acid and samarium chloride hexahydrate (SmCl3 ·6H2 O). The chemical structure of DTSm was confirmed by FTIR, XPS, ICP-OES and elemental analysis. The results of the accelerated thermo-oxidative aging tests, FTIR-ATR, TGA, methanol extraction experiments, whiteness and yellowness index revealed that DTSm significantly improved the long-term thermo-oxidative aging resistance of styrene-butadiene rubber/silica composites without discoloration, and the DTSm exhibited excellent volatility resistance and solvent extraction resistance. The outstanding antioxidative ability of DTSm for SBR/silica composites was attributed to the synergistic antioxidative effect between hindered phenols and samarium ions due to its excellent thermal stability and volatility resistance. This research is fruitful for the preparation of long-term highly aging-resistant rubber composites. Graphical Abstract: Image, graphical abstract